EFEKTIFITAS TOKEN EKONOMI UNTUK MENINGKATKAN PENGGUNAAN TANGAN KANAN PADA PERILAKU MAKAN ANAK KIDAL - Julika, Sari (EMPATHY Jurnal Fakultas Psikologi, 2014)
ABSTRACTLeft handed is a preference of someone who like to use their left hand to do an activities more than use their right hand. In east culture, the society is respect of right hand to do their activities, include when they eat. Using left hand when eat is impolite in east culture. This is make a problem with left handed people who like to use their left hand so they must adapt with east culture to not deviated by the society. The purpose of this research is to know the effectivity of token economy as one of kind behavior modification to increase the use of right hand in eating behavior with left handed child. The method was used to collection data is observational checklist. Data is analyse with visual inspection to compare the effectivity of the treatmnet. From the research is known that there are increase of the use of right hand in eating behavior at subject. The conclusion of this research is token economy effectives to increase the use of right hand in eating behavior with left handed child.Key word : left handed, right hand, eating behavior.